A large pulmonary cavity replaced by a tuberculosis granuloma and healed during treatment of a patient with tuberculosis - Chen, Ling; Zhang, Jianyong; Zhang, Hong (The Journal of Infection in Developing Countries, 2018)
In the early stages of M. tuberculosis infection, lung tuberculosis (TB) granulomas are often formed at sites of infection to constrain the infection and can undergo healing in most cases or enlarge as the disease progresses in some cases. We present here an unusual case of TB in which a large previously existing pulmonary cavity was replaced by a TB granuloma and then healed during treatment of a patient with poly-resistant TB. This case indicates that the disease process from TB granuloma formation to pulmonary cavities and progression or healing is more diverse than previously thought and could be reversed. An in-depth understanding of the disease process from initiation and maintenance of the TB granuloma to pulmonary cavities and progression or healing will provide new ways to combat mycobacterial infections.